Preliminary Study: Expulsive Effect of Empagliflozin on Small Lower Ureteric Stones in Type II Diabetic Patients - Alsayed S. Abdelaziz; Mohab AS. Abdalaziz; Mostafa M. Ebraheem; Ali A. Raheem; Ayman M. Ghoneem (Al-Azhar Assiut Medical Journal)
Background and aim Currently, a new oral diabetes medication comprises inhibition of the sodium-glucose co-transporter 2 (SGLT2), resulting in glycosuria, which may have a dislodging impact on stone ureter. The purpose of this trial was to examine and compare efficacy of empagliflozin in treatment of ureteric stones in type 2 diabetes patients with tamsulosin. Methods Between July 2018 and March 2020, 111 diabetic patients coming to urology outpatient clinics with a single 5–10 mm lower ureteral stone were randomly assigned to two groups: Empagliflozin group (Group A, n=54): Patients got an oral dose of 10 mg of empagliflozin once daily, and Tamsulosin group (Group B, n=57): Patients received tamsulosin 0.4 mg once daily but no SGLT2 inhibitor. The spontaneous passing stones, time required for expulsion, and unfavorable effects were assessed. Results There were no significant variations in baseline characteristics between the two groups of patients. In groups A and B, stone expulsion was reported in 75.9% and 77.1% respectively. In group A, the average time to expulsion was 11±4 days, while in group B, it was 13±6 days. The rate of spontaneous stone passage was insignificantly greater in group B, although the stone expulsion time was insignificantly shorter in group A than in group B. The unfavorable effects identified in both groups were comparable in severity and mildness. Conclusions In comparison to 0.4 mg tamsulosin, empagliflozin is a safe and efficient medical expulsive therapy for solitary lower ureteral stones < 10 mm in type 2 diabetes individuals.